2009
DOI: 10.1007/s11255-009-9661-7
|View full text |Cite
|
Sign up to set email alerts
|

No need for an “expiry date” in chronic peritoneal dialysis to prevent encapsulating peritoneal sclerosis

Abstract: Encapsulating peritoneal sclerosis (EPS) is drawing attention to the PD community because of its unpredictable onset and high mortality.Recently, the Scottish Renal Registry [1] has established the incidence of EPS and its correlation with PD duration in that region. The rate of EPS among patients on PD was 1.5%, with an incidence of 4.9 per 1,000 person-years. This rate is well within those reported previously (0.7-3.3%) [2][3][4][5][6][7]. Interestingly, the EPS rate increased with longer duration of PD up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The clinical implication is that a prolonged clinical vigilance and a high index of suspicion for the diagnosis are warranted. Furthermore, our findings contribute to the ongoing discussion whether young PD patients should prematurely be transferred to HD after a few years of PD while awaiting transplantation or after transplant failure (20,21).…”
Section: Discussionmentioning
confidence: 65%
“…The clinical implication is that a prolonged clinical vigilance and a high index of suspicion for the diagnosis are warranted. Furthermore, our findings contribute to the ongoing discussion whether young PD patients should prematurely be transferred to HD after a few years of PD while awaiting transplantation or after transplant failure (20,21).…”
Section: Discussionmentioning
confidence: 65%
“…There is no clear consensus regarding the optimal time on PD (27). It is obvious that shifting the patient to HD when necessary rather than continuing a therapy that is becoming dangerous will affect the patient's survival.…”
Section: Discussionmentioning
confidence: 99%
“…8 The medical therapy of EPS consists of bowel rest using total parenteral nutrition (TPN), corticosteroids, tamoxifen and immunosuppressive agents with recent use of inhibitors of mammalian target of rapamycin (mTOR) and avoiding or minimization of CNI administrations in patients with history of PD treatment. [9][10][11] Two experimental studies on chlorhexidine gluconate 0.1% EPS model showed that oral mTOR inhibitors (sirolimus and everolimus) significantly reduced peritoneal thickness, vascularity and fibrosis score. 12,13 This effect of mTOR inhibitors on the peritoneum was mediated by inhibition of fibrosis and neoangiogenesis through various molecular mechanisms including increased expression of E-cadherin (a protective gene for EMT) and decreased a-smooth muscle actin (a-SMA).…”
Section: Introductionmentioning
confidence: 99%